The Effect Of Service Quality And Price Perception On Repurchase Intention Through Customer Satisfaction Citilink Juanda Airport Surabaya - Hilda Khuzaifah; Ignatia Martha Hendrati; Sugeng Purwanto (LPPM Universitas Trunojoyo Madura, 2023)
This study aims to test the effect of service quality and price perception on repurchase intentions through customer satisfaction as an intervening variable at Juanda Airport Surabaya for Citilink airlines. This research is descriptive and quantitative using SEM-PLS analysis tool with the help of Smart-PLS software. The data consisted of primary data collected from 102 respondents using accidental sampling to determine the sample. The results show that the quality of service has a tremendously positive influence on repurchase interest, but price perception has no significant effect. Customer satisfaction influences an intervening variable between service quality and repurchase intent but does not exist as an intervening variable between price perception and repurchase intent. Based on the historical background discussed and in comparison with the results of previous studies, this study attempts to examine the relationship among service quality, customer satisfaction, price perception, and repurchase interest of Citilink Airlines located at Juanda Airport in Surabaya. Taking case studies at this airport is because Juanda Airport is the main base of Citilink airlines and is one of the main airports with a relatively high passenger density in Indonesia.